Mā te whiritahi, ka whakatutuki ai ngā pūmanawa ā tāngata = Together weaving the realisation of potential : exploring the social, cultural and health benefits of whānau-centred initiatives : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Health Science at Te Kunenga ki Pūrehuroa (Massey University), Manawatū, Aotearoa New Zealand - Reweti, Angelique (Massey University, 2022)
The persistence of Māori health inequities, exacerbated by deficit narratives, underscores the importance of conducting research on the strengths and capabilities whānau possess and use in their daily lives in order to actively rethink and redesign health promotion practice in Aotearoa New Zealand in a way that will be beneficial for whānau. Focusing on health promotion within an Indigenous context, this thesis synthesises results from three case studies about whānau-centred initiatives where Māori (Indigenous to New Zealand) values and practices are foundational. A kaupapa whānau research framework, developed in collaboration with whānau, draws on mātauranga (Māori epistemologies/ways of knowing) expressed in pūrākau (epistemological narratives), tikanga (cultural principles), te reo (Māori language), and lived experience, which serve as the foundation for the methodology employed in this research. The findings illustrate the diversity and potential capabilities of whānau-centred initiatives in addressing Māori health inequities, emphasising the critical role of whānau in improving Māori health and wellbeing. A conceptual framework, Tū Kahikatea, is developed to present findings demonstrating the connection between the values underpinning the initiatives and their outcomes. Furthermore, the framework emphasises how whānau-centred initiatives can aid whānau in achieving mana motuhake (mana achieved through collective self-determination and control over one’s own destiny). Consistent with an Indigenous approach to health promotion, this research indicates that health promotion activities that take into account Māori worldviews and values, as well as those generated within Māori communities, will have a greater influence on Māori health outcomes than programmes that take a top-down, single issue approach to health promotion. As part of a global movement for more inclusive healthcare that prioritises Indigenous voices and knowledge systems, this research bridges the gap between academia and local flax roots community action. With new opportunities created by recent changes to Aotearoa New Zealand's health system, findings highlight the diversity and potential of whānau-centred initiatives, and advocate for the continuation of current strengths-based whānau ora practices as a strategy to attain mana motuhake within whānau and thus improve whānau health outcomes.
Listed in 2022 Dean's List of Exceptional Theses
Keywords: Maori (New Zealand people); Health and hygiene; New Zealand; Families; Health promotion; Tāngata whenua; Hauora; Hauroa whanau; Māori Doctoral Thesis; Dean's List of Exceptional Theses; 451007 Te whakatairanga hauora o te Māori (Māori health promotion)